A cross-cultural validation of the psychological contract of safety on construction sites. (September 2021) - Newaz, Mohammad Tanvi; Wang, Dan; Davis, Peter; Wang, Xueqing; Jefferies, Marcus; Sheng, Zitong
Highlights: We investigate a cross-domain perspective of PCS on the construction worker's safety behaviour. Invariance of the Psychological Contract of Safety (PCS) model was found in Australia and China. The Chinese workers placed higher PCS influence on both compliance and participation behaviour than the Australian workers. Abstract: A Psychological Contract of Safety (PCS), based on mutual obligations between supervisors and workers, has been observed in an Australian construction context applied to safety. It has been described in recent research explaining the influential role of supervisors. In the past, there have been numerous studies establishing that the mainstream theory of the Psychological Contract (PC) affects behaviour when applied to various cultural backgrounds. Despite this, there is no established theory that explains how PCS may influence workers' behaviour in alternative cultural backgrounds. To test this theory, data were collected from construction projects in two divergent cultures, Australian and Chinese. A sample of 352 Australian and 374 Chinese construction workers completed a survey related to PCS and its influence on safety behaviour. Results from using Structural Equation Modelling show that there is a strong influence of the PCS on the safety behaviour of individual workers in both countries. Specifically, the Chinese workers placed higher PCS influence on both compliance and participation behaviour than the Australian workers. The research findings have been contextualized with managerial and cultural implications allowing practitioners to apply the mechanism to improve safety behaviours of workers in their respective cultural contexts. Conceptualising the extant PC theory as a framework from which to leverage PCS management initiatives brings a new approach to construction safety studies, revealing the influential role of supervisors in interpreting safety obligations in a cross-cultural construction setting.